Identification of oxide defects in semiconductor devices: A systematic approach linking DFT to rate equations and experimental evidence. (August 2018) - Goes, W.; Wimmer, Y.; El-Sayed, A.-M.; Rzepa, G.; Jech, M.; Shluger, A.L.; Grasser, T.
Abstract: It is well-established that oxide defects adversely affect functionality and reliability of a wide range of microelectronic devices. In semiconductor-insulator systems, insulator defects can capture or emit charge carriers from/to the semiconductor. These defects feature several stable configurations, which may have profound implications for the rates of the charge capture and emission processes. Recently, these complex capture/emission events have been investigated experimentally in considerable detail in Si/SiO2 devices, but their theoretical understanding still remains vague. In this paper we discuss in detail how the capture/emission processes can be simulated using the theoretical methods developed for calculating rates of charge transfer reactions between molecules and in electro-chemistry. By employing this theoretical framework we link the atomistic defect configurations to known trapping model parameters (e.g. trap levels) as well as measured capture/emission times in Si/SiO2 devices. Using density functional theory (DFT) calculations, we investigate possible atomistic configurations for various defects in amorphous ( a )-SiO2 implicated in being involved in the degradation of microelectronic devices. These include the oxygen vacancy and hydrogen bridge as well as the recently proposed hydroxyl E ′ center. In order to capture the effects of statistical defect-to-defect variations that are inevitably present in amorphous insulators, we analyze a large ensemble of defects both experimentally and theoretically. This large-scale investigation allows us to prioritize the candidates from our defect list based on their trap parameter distributions. For example, we can rule out the E ′ center as a possible candidate. In addition, we establish realistic ranges for the trap parameters, which are useful for model calibration and increase the credibility of simulation results by avoiding artificial solutions. Furthermore, we address the effect of nuclear tunneling, which is involved according to the theory of charge transfer reactions. Based on our DFT results, we demonstrate the impact of nuclear tunneling on the capture/emission process, including their temperature and field dependence, and also give estimates for this effect in Si/SiO2 devices.